1990
DOI: 10.1021/jo00300a035
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of carbonyl compounds with ethyl lithiodiazoacetate. Studies dealing with the rhodium(II)-catalyzed behavior of the resulting adducts

Abstract: shown by GLC analysis and 13C NMR to contain 5a (lo%), unknown compounds (12%), and 3a (78%). The data (GLC and '3c NMR) are identical with those from the products from reaction of 1 with methanol a t room temperature. Acknowledgment. We acknowledge grants from the Research Committee of the New Zealand Universities J. Org. Chem. 1990,55, 4144-4153 Grants Committee and helpful discussions with Professor M. A. Battiste.Supplementary Material Available: 13C and 'H NMR spectra for compounds 1,3a-d, 5a,b, 6a,b, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(42 citation statements)
references
References 12 publications
0
40
0
2
Order By: Relevance
“…[34a] Applying the optimised catalyst ± solvent combination for intermolecular cycloaddition of a-diazoketones with DMAD reported by Hashimoto [34a] (catalyst 24, PhCF 3 as solvent) to 2-diazo-3,6-diketoester 2 c at 25 8C resulted in only essentially racemic cycloadduct 3 c (90 % yield, 1 % ee). Furthermore, cycloadduct 25 (R 1 CO 2 Et, R 2 Me) [35] was obtained in only 33 % ee under the same conditions in the reaction of 2-diazo-3,6-diketoester 23 (R 1 CO 2 Et, R 2 Me) [35] with DMAD [a-diazoketone 23 (R 1 H, R 2 Me) gave cycloadduct in 80 % ee]. [34a] These last results indicate that ee is rather sensitive to variation in the electronic structure of the dipole.…”
Section: Resultsmentioning
confidence: 99%
“…[34a] Applying the optimised catalyst ± solvent combination for intermolecular cycloaddition of a-diazoketones with DMAD reported by Hashimoto [34a] (catalyst 24, PhCF 3 as solvent) to 2-diazo-3,6-diketoester 2 c at 25 8C resulted in only essentially racemic cycloadduct 3 c (90 % yield, 1 % ee). Furthermore, cycloadduct 25 (R 1 CO 2 Et, R 2 Me) [35] was obtained in only 33 % ee under the same conditions in the reaction of 2-diazo-3,6-diketoester 23 (R 1 CO 2 Et, R 2 Me) [35] with DMAD [a-diazoketone 23 (R 1 H, R 2 Me) gave cycloadduct in 80 % ee]. [34a] These last results indicate that ee is rather sensitive to variation in the electronic structure of the dipole.…”
Section: Resultsmentioning
confidence: 99%
“…The spectroscopic data of this compound, which was obtained in 71% yield, are in agreement with that previously related in literature. 38,39 4.4.3. 2-Carboisobutoxycyclohexanone (3c).…”
Section: -Carbomethoxycyclohexanone (3a)mentioning
confidence: 99%
“…9) The following dehydration of β-hydroxy diazo carbonyl compounds (5a, b) was quite challenging considering the relative labile character of diazo group. We systematically screened several conditions including the common dehydration condition i.e., excessive phosphorus oxychloride in pyridine, 10) which failed to provide a desirable yield. Finally, we found that when the combination of (CF 3 CO) 2 O and Et 3 N in CH 2 Cl 2 was employed, the vinyl diazo carbonyl compounds (6a, b) were obtained in 84-90% yield.…”
Section: Resultsmentioning
confidence: 99%